Bovine colon organoids: From 3D bioprinting to cryopreserved multi-well screening platforms. (December 2019) - Töpfer, Elfi; Pasotti, Anna; Telopoulou, Aikaterini; Italiani, Paola; Boraschi, Diana; Ewart, Marie-Ann; Wilde, Colin
Abstract: Three-dimensional (3D) colon organoids, termed "colonoids", derived from adult stem cells represent a powerful tool in in vitro pharmaceutical and toxicological research. Murine and human colonoid models exist. Here we describe the establishment of bovine colonoids for agri-biotechnological applications, and extend the repertoire of colonoid culture options through proof-of-principle for bioprinting and novel in-plate cryopreservation technology. As a first step, we differentiated established long-term bovine colonoid cultures into mature colonoids. Tissue-specific differentiation was demonstrated by gene expression. Second, we investigated cryopreservation of colonoids in situ within an extracellular matrix in multi-well plates. Upon controlled thawing, cryopreserved 3D cultures grew at similar rates to unfrozen colonoids. Cytotoxic sensitivity to staurosporine was not significantly different between in situ freeze-thawed and unfrozen control cultures. Third, scalability of colonoid culture assembly by extrusion bioprinting into multi-well plates using GelMA bioink was assessed. With optimised bioprinting and crosslinking parameters, colonoids in GelMA were printed into 96 well culture plates and remained viable and proliferative post-print. For tissue-relevant in vitro studies we furthermore established differentiated colonoid-derived monolayer cultures on permeable membranes. Taken together, we outline novel in vitro approaches to study the ruminant colonic epithelium and introduce in-plate cryopreservation as convenient alternative to conventional in-vial cryopreservation. Highlights: Culture methodology for bovine 3D colonoid long-term culture. Novel in situ cryopreservation technique of 3D colonoid cultures in multi-well plates for subsequent screening assays. Proof-of-principle for suitability of bovine colonoids in 3D extrusion bioprinting. Differentiated epithelial monolayer formation from bovine colonoids.